PENGELOLAAN DAYA TARIK OBJEK WISATA TAMAN NASIONAL ZAMRUD KABUPATEN SIAK PROVINSI RIAU - Br Siahaan, Dian Irma Evie Br Siahaan; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Conservation is a from of human attemp to preserve the nature. One example of conservations is national park which covers a large area with pristine ecosystems. Therefore, national parks are the answer to the high rate of natural damage that has occured. This research was conducted to determine the visitorâ€™s perspective toward the Attraction Management of Zamrud National Park in Siak Regency, Riau Province. This Study aims to describe the attractiveness and management of Zamrud National Park by using a combination of quantitative and qualitative methods to classifyÂ the problems raised in this study. The data collection techniques used in this study were observations, interviews, questionnaires, and documentation. The results of this study indicate that visitors strongly agree that the attraction of Zamrud National Park tourist attraction has been carried out well based on the research that had been done.Keyword: National Park, Attraction, Management